Global research trends between gut microbiota and lung cancer from 2011 to 2022: A bibliometric and visualization analysis - Chen, Haitao; Lai, Yuebiao; Ye, Chenxiao; Wu, Changhong; Zhang, Jiali; Zhang, Zewei; Yao, Qinghua (Frontiers in Oncology, 2023)
Background: Increasing number of studies have found that the gut microbiota was related to the occurrence and development of lung cancer. Nonetheless, publication trends and research hotspots in this field remain unknown. The study aimed to perform a bibliometric analysis to systematically identify publication trends and research hotspots in the field of gut microbiota and lung cancer research within a 12-year panorama. Methods: Publications related to gut microbiota and lung cancer between January 1, 2011, to October 25, 2022, were retrieved from the Web of Science core collection (WoSCC) database. The online analytic tool of the WoSCC was used to analyze various bibliometric parameters. Bibliometrics website, CiteSpace, and VOSviewer were used to identify research trends and hotspots. Results: A total of 375 publications related to gut microbiota and lung cancer were extracted from WoSCC and identified to analysis. The number of annual publications has grown rapidly since 2018, and reached a peak in 2022. China was the most prolific country in this field, with 120 publications, followed by the United States (114), with the highest H-index of 31. Additionally, France ranked the highest with an average of 133 citations, while the leading institution and journal was the Unicancer and the International Journal of Molecular Sciences, respectively. Interestingly, Routy Bertrand was the most prolific author, and also the most cited author in terms of H-index and citations. References and keywords burst detection indicated that the research hotspots mainly included (1) gut microbiota directly affects the efficacy of immunotherapy for lung cancer, (2) the application of different gut bacteria on lung cancer, and (3) the mechanism of gut microbiota on lung cancer. Conclusion: The findings of this study revealed the general publication trends and evolving research hotspots in the field of gut microbiota and lung cancer at a global level. The research hotspots focused on the clinical application of gut microbiota combined with immunotherapy in lung cancer and its mechanism. The findings of this study provide new perspectives on the field, which may shed light on a beneficial impact on further etiological studies, diagnosis, and treatment for lung cancer.